Hand Function and Hand-Eye Coordination in Cervical Conditions – A Cross Sectional Study - Kumar B, Senthil; R, Arunachalam (Clinical Medicine And Health Research Journal, 2024)
Background of the study: Cervical Conditions are most common orthopaedic condition that may affect a large number of people. It compresses the nerve roots and may cause muscle weakness, numbness and loss of fine movements of the upper limbs. Hand Functions are movements of the hand and Hand eye coordination is the coordination of motor and visual inputs to produce a movement. This study helps to find out whether the hand function and hand eye coordination are affected in Cervical Conditions. Aim: Aim of this study is to find whether the hand function and hand eye coordination are affected in Cervical Conditions. Method: A total number of 212 subjects with cervical pain were screened for the study inclusion criteria and 132 subjects were selected for the study. The assessment of hand function, hand-eye coordination skills and shoulder disability were carried out for all the Subjects. NDI scale was used to evaluate the subject’s severity of pain and the associated disability among the samples. Hand function we evaluated using Purdue pegboard. Ball Tossing Task and Wall Ball Bounce Task were done to assess the Hand eye coordination. Results: On assessing the correlation between NDI and PURDUE, the results obtained on analysis is -0.108, which shows a negative relationship between the variables. The non-parametric correlation analysis using the spearman’s rho between the Neck disability index (NDI) with the PURDUE is -0.053, which shows a negative relationship between the variables. On assessing the correlation between NDI and Hand-Eye Task-1, the results obtained on analysis is -0.0081, which shows a negative relationship between the variables and the non-parametric correlation analysis is -0.162, which shows a negative relationship between the variables. On assessing the correlation between NDI and Hand-Eye Task-2, the results obtained on analysis is -0.023, which shows a negative relationship between the variables and the non-parametric correlation analysis is -0.092, which shows a negative relationship between the variables. Discussion: The purpose of the study is to find whether the hand function and hand eye coordination are affected in Cervical Conditions. Conclusion: This study concludes that the hand function and hand eye coordination are not affected in Cervical Conditions.